General allometric scaling of net primary production agrees with plant adaptive strategy theory and has tipping points. (30th January 2017) - Jenkins, David G.; Pierce, Simon
Summary: Allometric scaling of net primary production (NPP) with plant biomass (B) is important to ecological carbon dynamics and energetics. Metabolic theory predicts a nonlinear power law for NPP scaling, based on fractal vascular systems, resulting in a linear model when using log NPP/log B axes that are standard in allometry. Alternatively, two other hypotheses predict nonlinear models for log‐transformed data, with potential tipping points. Size‐based competition may cause a quadratic curve as larger plants limit NPP by smaller plants. More inclusively, the plant adaptive strategies hypothesis predicts a sigmoidal curve to represent those same competitive effects, plus stress and ruderal adaptations that maintain relatively low NPP in habitats that are abiotically limiting or disturbed. We evaluated all three hypotheses for terrestrial vascular plants, using information theoretic model selection based on the Akaike Information Criterion (AICc). Published data ( N = 709) were organised in subsets according to reported organisational level and plant growth form. Alternative curves were compared for a general model (using all data) and per subset. Potential tipping points were estimated using segmented regression. The plant adaptive strategies hypothesis was supported in general (AICc weight = 1·00) and via internal consistency for five of six subsets (86% of data). Competition was supported as affecting NPP at greater B, where quadratic and sigmoidal models often coincided. Only non‐woody assemblages most plausibly fit a power law model, perhaps related to sparse data at lowest B. Synthesis . Adaptive strategies and corresponding environmental conditions appear to constrain terrestrial net primary production scaling relative to metabolic theory's ideal. Moreover, tipping points in general nonlinear net primary production scaling (at c. 38 and 360 g m −2 B) indicate thresholds for rapid changes in net primary production given changing B that occurs via changing climate, human appropriation and land use. Abstract : Adaptive strategies and corresponding environmental conditions appear to constrain terrestrial NPP scaling relative to metabolic theory's ideal. Moreover, tipping points in general nonlinear NPP scaling (at c. 38 and 360 g m −2 B) indicate thresholds for rapid changes in NPP given changing B that occurs via changing climate, human appropriation and land use.